Activated carbon nanofibers incorporated metal oxides for CO2 adsorption: Effects of different type of metal oxides. Issue 45 (March 2021) - Othman, Faten Ermala Che; Yusof, Norhaniza; Samitsu, Sadaki; Abdullah, Norfadhilatuladha; Hamid, Muhammad Faris; Nagai, Kazukiyo; Abidin, Muhammad Nizam Zainal; Azali, Mohd Ariff; Ismail, Ahmad Fauzi; Jaafar, Juhana; Aziz, Farhana; Salleh, Wan Norharyati Wan
Highlights: Effects of incorporation of different types of metal oxides on physicochemical properties of ACNFs composites. ACNFs/MgO exhibits the highest SBET and CO2 adsorption capacity. CO2 adsorption on the resultant ACNFs incorporated metal oxides involved physisorption and chemisorption, simultaneously. Abstract: Activated carbon nanofibers (ACNFs) incorporated with four different types of metal oxides; magnesium oxide (MgO), manganese dioxide (MnO2 ), zinc oxide (ZnO), and calcium oxide (CaO) were successfully prepared via a simple electrospinning and pyrolysis process. Optimum electrospinning and pyrolysis parameters were performed to obtain porous ACNFs composites for CO2 capture. The porous and textural characteristics of the resultant ACNFs composites were performed using N2 adsorption isotherms at 77 K, while the features and morphologies were observed using TEM and FE-SEM. The EDX and Raman analysis were used to determine and analyse the elemental composition in the ACNFs. It was observed that ACNFs incorporated MgO (ACNF2) exhibited the largest surface area (413 m 2 /g) and the highest micropore volume (0.1777 cm 3 /g) as compared to pristine ACNF (ACNF1) and other ACNFs composites. ACNF2 also possessed the smallest fiber diameter of 357.8 ± 16.7 nm as compared to other samples. The successful incorporation of all metal oxides in electrospun fibers were proven by EDX analysis. All resultant ACNFs exhibited D- and G-peaks in Raman spectra indicating the carbon-based materials structure. As expected, the ACNF2 attained the highest CO2 adsorption of 60 cm 3 /g at 298 K as compared to other ACNFs samples which is correspond to N2 adsorption capacity. The CO2 adsorption/desorption isotherms of the best composite sample (ACNF2) was measured at three different temperatures (273, 298, and 318 K) at 1 bar through a volumetric adsorption process and this result was compared to ACNF1. It shown that the CO2 adsorption capacity is inversely proportional to the increasing temperature in which as the adsorption temperature increased, the adsorbed amounts of CO2 decreased. These results indicated that the incorporation of MgO into ACNFs shows the best improvement in their physicochemical properties for enhanced adsorption performance of CO2 under practical conditions.